Experiments in Modern Living: Scientists' Houses in Canberra 1950-1970 - Cameron, Milton (ANU Press, 2012)
When a group of brilliant young scientists arrived in Australia's national capital after World War II to take up leading roles in the establishment of national research institutions, they commissioned Australia's leading architects to design their private houses. The houses that resulted from these unique collaborations rejected previous architectural styles and wholeheartedly embraced modernist ideologies and aesthetics. The story of how these progressive clients contributed to the innovative design of their houses brings fresh insights to mid-twentieth-century Australian domestic architecture and to Canberra's rich cultural history.